ANALISIS ALOKASI DANA CORPORATE SOCIAL RESPONSIBILITY SERTA PELAPORAN SUSTAINABILITY REPORT BERDASARKAN GLOBAL REPORTING INITIATIVE (GRI G3) DI PT. PEMBANGKITAN JAWA BALI - Putranti Budi Maygarindra; Rovila El Maghviroh (The Indonesian Accounting Review, 2012)
This study tries to analyze for allocation of Corporate Social Responsibilitys funds and reportingof sustainability report according to Global Reporting Initiative (GRI G3) at PT.Pembangkitan Jawa Bali (PJB). This study used interview and observation to obtain the requireddata for analysis. From the results of the analysis CSR budget of PT. PembangkitanJawa Bali (PJB) can be concluded that there are areas of education, social & economiccommunity, health, environment & security and public order. In each of these fields, a divisionof CSR budget each 25% of the total budget. From the results of the analysis of researchon CSR activities carried out, can be seen that the education budget which absorbed 20.29%,social & community economic absorbed 28.5%, 23.24% absorbed health, environment &security and public order 28.08 %. While the results of analysis of sustainability report accordingto Global Reporting Initiative (GRI G3), the company did not disclose some of theitems on each standard in detail in the sustainability report, but the whole aspect was reportedin outline and PT. Pembangkitan Jawa Bali (PJB) is not according to Global ReportingInitiative (GRI G3) in reporting sustainability report.